Factors Influencing Healthcare Professionals’ Knowledge, Attitude, and Self-efficacy in CPR: A systematic review - Nik Hassan, Nik Hasmumthaj; Ahmad Sharoni, Siti Khuzaimah; Hamina, Dathini (Environment-Behaviour Proceedings Journal, 2025)
Cardiopulmonary Resuscitation (CPR) is a vital lifesaving intervention for cardiac arrest. The systematic review is to investigate CPR knowledge, attitude, self-efficacy, and influencing factors among health professionals. This review analyzed cross-sectional studies published from 2019 to 2024 using data sources from PubMed, Scopus, and Google Scholar. The result revealed a good knowledge ranging from 11.9% to 89.5%. Approximately 65.0% had positive attitudes, and 89.4% positive self-efficacy. Affecting factors include age, work experience, CPR training, specialty area, and exposure to cardiac arrest cases. The findings highlight the importance of standardized and frequent CPR training, leading to improved quality of care.